Studying and influence of professional motivation of students when studying graphic disciplines - Tarantey , Victor; Tuleuova, Gulmarzhan; Karipbayev , Zhassulan (Рroblems of engineering and professional education, 2024)
This article explores the issues of quality management in teaching graphic disciplines in higher technical education. Special attention is given to the need for continuous monitoring of students' academic performance, incorporating various assessment methods such as written assignments, oral examinations, computer-based testing, and independent project defense. Analyzing the correlation between these assessment methods allows for a more objective evaluation of students' knowledge levels and helps identify weaknesses in the educational process, contributing to its optimization and increased efficiency. As part of the study, a survey was conducted among students majoring in "Architecture" and "Design" to examine their professional motivation and interest in the subject "Engineering Graphics." The results showed that many students do not fully recognize the importance of engineering graphics in their future careers, which negatively affects their motivation to study the subject. At the same time, the findings revealed that incorporating modern educational technologies and practice-oriented teaching methods contributes to a deeper understanding of the material. The article also discusses possible ways to enhance the teaching of engineering graphics, including the integration of digital technologies, increasing the number of practical lessons, and implementing an individualized approach to learning.